2020
DOI: 10.3390/healthcare8030335
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Cognitive–Motor Rehabilitation in Older Adults with Mild Cognitive Impairment: A Randomized Controlled Study on Motivation and Cognitive Function

Abstract: The purpose of this study was to investigate the effects of virtual reality-based cognitive–motor rehabilitation (VRCMR) on the rehabilitation motivation and cognitive function in older adults. This study enrolled 40 older adults with mild cognitive impairment (MCI), living in the community. The subjects were randomly assigned to a VRCMR group (n = 20) or a conventional cognitive rehabilitation (CCR) group (n = 20). The VRCMR group underwent VRCMR using MOTOcog, a computer recognition program, whereas the CCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 33 publications
3
82
0
Order By: Relevance
“…Cognitive rehabilitation using virtual reality can help improve cognitive function in older adults with cognitive impairment or dementia. This is in line with research conducted by (Park, Jung and Lee, 2020), where his research stated that participants who have been given virtual realitybased cognitive rehabilitation interventions to carry out various daily activities such as driving, bathing, cooking, and studying can stimulate several cognitive aspects such as attention, memory, problem problems, and executive training.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Cognitive rehabilitation using virtual reality can help improve cognitive function in older adults with cognitive impairment or dementia. This is in line with research conducted by (Park, Jung and Lee, 2020), where his research stated that participants who have been given virtual realitybased cognitive rehabilitation interventions to carry out various daily activities such as driving, bathing, cooking, and studying can stimulate several cognitive aspects such as attention, memory, problem problems, and executive training.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, physical exercise can stimulate the hypothalamic, pituitary, and adrenal axes which increase cortisol levels which increase thinking and memory skills. The results of this study indicate that the quality improvement in memory function is calculated by a cognitive assessment using the Montreal Cognitive Assessment (MoCA) scale, especially on the aspects of memory and attention (Park, Jung and Lee, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…After reviewing the full texts, 22 trials were included for primary analysis. Then, two studies with low cognitive scores measured by the MoCA 34 and MMSE, 22 one study with large variation 19 and two studies with high risk of bias 35,36 were removed. A total of 17 studies of VR cognitive training in individuals with MCI were included.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…16 Some recent original studies of the effects of VR on cognitive function have added new evidence to the field, and individuals with MCI are a popular interventional population for VR cognitive training. 12,17,19 The results of experimental studies focusing on the effects of VR cognitive training in individuals with MCI have not been consistent; some have indicated that VR cognitive training has positive effects, [20][21][22] while others have reported no effects. 17,19,23…”
Section: Introductionmentioning
confidence: 99%
“…Park et al conducted a randomized control trial to compare the effectiveness of virtual reality-based cognitive-motor rehabilitation (VRCMR) with conventional cognitive rehabilitation (CCR) in patients with MCI. The trial demonstrated that VRCMR can enhance motivation for rehabilitation and cognitive function in older adults with MCI better than CCR [15]. However, it is not clear if the improvement in cognitive functioning in this study is due to use of VR-based immersive environment or incorporation of motor rehabilitation in the VRMCR programs.…”
Section: Introductionmentioning
confidence: 69%